Pemanfaatan Media Game Edukasi Berbasis Android untuk Pengembangan Kognitif Anak Usia 5-6 Tahun di TK Barunawati Ampenan Tahun 2022 - Dinda Riris Nurviani Putri; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2022)
Cognitive development in early childhood requires an intermediary in the form of learning media so that children can concentrate longer and can distract children who are easily bored. During a pandemic in this era of globalization, one way that can be used for cognitive development in children is to utilize the Android-based educational game Stickman Party as a medium for cognitive development in early childhood. This study uses field research methods with a descriptive qualitative approach. Data collection techniques using three techniques, namely observation, interviews and documentation. While the coming analysis technique used is the Miles and Humberman model which consists of three types of analysis activities namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the use of the Android-based educational game Stickman Party as a medium for cognitive development in early childhood at Barunawati Ampenan Kindergarten can develop cognitive and focus on children through three applications. First, provide educational game media Stickman Party on Android then provide directions and explanations about the benefits and how to learn to use Stickman Party, then ask children to try the games in the Stickman Party educational game. Second, the implementation of cognitive development is carried out with assistance when children use the StickmanParty educational game accompanied by giving a little understanding about cognition, then asking children to show how to solve problems in games asked by the teacher or their parents. Third, cognitive post-introduction is carried out after children use educational games, namely by deepening cognitive material that has been studied using the Stickman Party Educational Game application which shows several advantages, namely growing children's curiosity and creativity, as well as making the learning process interesting.